Ion-Tagged Phosphines as Ligands for Suzuki Coupling of Aryl Halides in a Phosphonium Ionic Liquid - Keith, Adam J.; Kosik, Stephen D.; Tillekeratne, L. M. Viranga; Mason, Mark R. (Synlett, 2014)
Gramine-based N-substituted phosphines were synthesized and utilized as ligands in Suzuki–Miyaura coupling of aryl bromides and chlorides in the room temperature ionic liquid trihexyltetradecylphosphonium bis(trifluoromethanesulfonyl)imide. Increased yields were achieved with ion-tagged ligands compared to ligands bearing pendant amines, likely due to higher solubility of the former. Cyclohexyl groups on the phosphine moiety generally resulted in higher yields than tert-butyl groups. In addition, a biphasic ionic liquid/water system outperformed catalysis in neat ionic liquid and provided higher yields at lower temperatures.
Keywords: palladium; catalysis; ionic liquids; cross-coupling; green chemistry